Analisis Strategi Mempertahankan dan Mengembangkan Bisnis di Tengah Pandemi COVID-19 Serta Mengetahui Dampak Perkembangan dan Pertumbuhan COVID-19 di Indonesia - Neng Frida (Jurnal Aktiva : Riset Akuntansi dan Keuangan, 2020)
The increase in cases caused by COVID-19 is very detrimental for all schools, such as restaurants, cinemas, cafes, tourism, trade and investment. In addition, the Corona Virus is very detrimental to all people, both middle, upper and lower classes because the businesses they run have suffered considerable losses during the pandemic and many layoffs or who know layoffs so that the number of unemployed causes poverty, the greatest impact is felt is the economy other than the economy and education is threatened, as well as in terms of the health of the cases affected by COVID-19 which has caused PSBB to never finish, thus hampering economic growth in exports, imports So that it becomes a concern for all people who maintain health and hygiene by keeping their distance when in a crowd and using masks and complying with health protocols so that the widespread reduction of spread. This is because it affects the sustainability of the economy which causes the economy to decline due to its awareness. Slowing economic growth, weakening market prices, weakening income and disrupting productivity. For all sectors, both from the trade sector or MSMEs, a change is needed to maintain a business by switching to E-Commers who trade using social media networks that rely on the internet. The research method used in this research is qualitative analysis with exploratory steps with participatory observation techniques. The results of the research on survival strategy recommendations for MSMEs are in the form of trading electronically, doing digital marketing, making product improvements and adding services as well as establishing and optimizing marketing customer relationships. The results of research are important to be carried out by business people and it is hoped that business people will always be responsive and adapt to environmental changes in order to survive.